"Black Workers Matter": Black labor geographies and uneven redevelopment in post-Katrina New Orleans. Issue 3 (16th March 2021) - Keegan, Caroline
ABSTRACT: For low-wage, predominantly Black workers in the city of New Orleans, post-Hurricane Katrina redevelopments constructing the "New New Orleans" present revanchist spatial configurations of uneven development. Black workers are relegated to industries characterized by precarious, discriminatory, and low-paying jobs building and supporting an upscale, and tourist-focused economic infrastructure. These emerging social relations are embedded in, and have evolved out of, a longstanding "plantation tradition" of racial and economic subjugation of Black labor. Understanding the redevelopment of New Orleans as a continuation of a "plantation logic, " in conversation with geographical discussions of labor, this paper investigates Black labor geographies in the so-called "New New Orleans". The paper is based on interviews and participant observation with members and organizers of Stand with Dignity, part of the New Orleans Workers' Center for Racial Justice (NOWCRJ), which focuses on the concerns of un- and underemployed Black workers. Drawing on narratives of resistance, this research shows how the uneven development of (work)places has been met by demands for a New Orleans in which "Black Workers Matter."